The Use of CROWD Techniques in Reading Comprehension and Critical Thinking Skills in Children Aged 5-6 Years - Aviratri, Yudha (STAI Miftahul Ula Nganjuk, 2025)
Reading comprehension and critical thinking are essential foundations for developing reflective, problem-solving, and effective communication skills. However, national and international studies consistently reveal that Indonesian children remain weak in both aspects, particularly in early childhood—a critical period for literacy and cognitive development. This study examines the effectiveness of the CROWD technique (Completion, Recall, Open-ended questions, Wh-questions, and Distancing) in dialogic reading to enhance reading comprehension and critical thinking among children aged 5–6 years. Employing a mixed-method embedded design, the study combined quantitative data from non-equivalent control group experiments with qualitative data from classroom observations, teacher interviews, and child responses. Validated instruments were applied through expert judgment, Aiken’s V, Cronbach’s Alpha, and Cohen’s Kappa (? = 0.7), ensuring strong validity and reliability. The results of the Shapiro-Wilk test indicated normally distributed data (W = 0.957, p > 0.05), while Mann-Whitney U tests revealed significant differences between treatment and control groups. Children in the treatment group demonstrated substantially higher scores in CROWD responses (U = 139.33 vs. 39.33), reading comprehension (U = 122 vs. 22), and critical thinking (U = 120.66 vs. 20.66). Qualitative findings further highlighted that CROWD fostered reflective and associative thinking, though implementation required more time (22 minutes vs. 15 minutes). Overall, the study concludes that CROWD questions significantly improve children’s reading comprehension and critical thinking when integrated into read-aloud sessions. Future research should explore longitudinal impacts, optimize the number of CROWD items for efficiency, and extend applications to diverse literacy contexts such as home, libraries, or digital environments.